2004
DOI: 10.2134/agronj2004.1730
|View full text |Cite
|
Sign up to set email alerts
|

Row Configuration and Nitrogen Application for Barley–Pea Intercropping in Montana

Abstract: 1960; Walton, 1975; Carr et al., 1998; Chapko et al., 1991). Robinson (1960) reported that pea improved oat (Avena Intercropping barley (Hordeum vulgare L.) with Austrian winter sativa L.) forage yield. In a 2-yr pea-barley and pea-oat pea (Pisum sativum ssp. arvense L. Poir) may increase the use efficienintercropping study, Carr et al. (1998) found that total cies of growth resources and reduce fertilizer N requirements. The forage yield was unaffected by intercropping when the objectives of this study were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
85
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 27 publications
(48 reference statements)
23
85
2
2
Order By: Relevance
“…Minimum economical yield for lentil (15.3 g/m 2 ) was recorded in plots of sole lentil (Table 3) ) was recorded in plots where 2 rows B + 4 rows L but Maximum biological yield for barley (626.4 g/m 2 ) was recorded in plots where 3 rows B + 3 rows L were sown. Chen et al (2004) found that, under low fertility conditions, a 50:50 mixture of barley and pea yielded as well as pure stands of barley that agree by this results. Maximum weight of 1000 seed for lentil (15.1 g) was recorded in plots where 2 rows B + 4 rows L were sown but the maximum weight of 1000 seed for barley (38.9 g) was recorded in plots where 4 rows B + 2 rows L were sown.…”
Section: Resultssupporting
confidence: 85%
“…Minimum economical yield for lentil (15.3 g/m 2 ) was recorded in plots of sole lentil (Table 3) ) was recorded in plots where 2 rows B + 4 rows L but Maximum biological yield for barley (626.4 g/m 2 ) was recorded in plots where 3 rows B + 3 rows L were sown. Chen et al (2004) found that, under low fertility conditions, a 50:50 mixture of barley and pea yielded as well as pure stands of barley that agree by this results. Maximum weight of 1000 seed for lentil (15.1 g) was recorded in plots where 2 rows B + 4 rows L were sown but the maximum weight of 1000 seed for barley (38.9 g) was recorded in plots where 4 rows B + 2 rows L were sown.…”
Section: Resultssupporting
confidence: 85%
“…In these cases, total LER was significantly different (P < 0.01) and values were higher than one showing the advantage of intercropping over sole stands in regard to the use of environmental sources for plant growth [32]. Similar results were reported for mix-proportions of pea-barley [19], bean-wheat [10], and maize-faba bean [43]. Partial LER values also showed that, compared to soybean, cowpea appears to have more beneficial land use efficiency in all mixtures.…”
Section: Land Equivalent Ratio Area Time Equivalent Ratio and Relatisupporting
confidence: 69%
“…On the other hand, all partial LER of cowpea was lower than 0.5 except intercrops with 07SADVE, Samaru and VP0538 which indicates that there was a disadvantage for cowpea. The partial LER of soybean were higher than 0.5 for all intercrops which indicates that there was an advantage for soybean [19], except intercrops with 07SADVE and Samaru. LER showed the positive influences on growth and yield of maize and legumes intercrops (LER > 1) in maize-soybean intercrops with the greater for 08SADVE 1-soybean (1.66).…”
Section: Land Equivalent Ratio Area Time Equivalent Ratio and Relatimentioning
confidence: 83%
See 1 more Smart Citation
“…To meet this challenge, we need a detailed understanding of available genetic variation in N response, using field and controlled environment approaches to assess the responsiveness of genotypes to supplied N, and dissection of N metabolic pathways. However, NUE and N response are complex traits which show inconsistent trends across years and sites (Hirel et al 2001;Chen et al 2004;Brennan et al 2014). Accordingly, the integration of agronomic, physiological and molecular data will be important for selection of the best genotypes with high NUE in specific environments (Hirel et al 2007;Pathak et al 2008;Sylvester-Bradley and Kindred 2009).…”
Section: Introductionmentioning
confidence: 99%